Ambiguous belonging: Media practices among Syrians in Denmark. (1st April 2020) - Yonus, Zenia
This article presents two prevailing media orientations among Syrian migrants in Denmark. The purpose is to show how Syrians relate to, and evaluate, mediated content, and how it relates to political action. The orientations are dyadic, and represent both news about the conflict in Syria, as well as Danish politics – migration policies in particular. The first is the ambivalent-localizing orientation that mirrors the twofold orientation towards both Danish and Syrian political events; and the second is the informed-obliterate, in which Syrians choose to drop out of media content about Syria due to mental health issues, or fear for their families still in Syria. The study shows how media practices among diasporic Syrians in Denmark are multidimensional, and puts forward the complexities of identity processes between here and there, between political activism and demobilization, and between gratitude for being safe and never feeling safe. The argument is that, these multi-local processes involve multiple interdependent factors, diverse encounters, as well as a variety of struggles in belonging. Syrians consequently lack agency as well as social, media and political recognition.